Intermittent chemotherapy in metastatic androgen-independent prostate cancer - Beer, T M (Nature Publishing Group, 2003)
Intermittent use of chemotherapy for androgen-independent prostate cancer (AIPC) instead of treatment until disease progression may reduce toxicity. We prospectively tested this approach in eight AIPC patients responding to calcitriol plus docetaxel who reached a serum prostate-specific antigen (PSA) <4 ng ml(−1). Chemotherapy was suspended until a rise in PSA⩾50% and 1 ng ml(−1). The median duration of treatment holiday was 20 weeks (13–43+weeks) and all patients retained sensitivity to re-treatment. Chemotherapy holiday was associated with an improvement of fatigue (P=0.05). Intermittent chemotherapy for AIPC is feasible and deserves further study.